1994
DOI: 10.1126/science.7801126
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acylation of Two Internal Lysine Residues Required for the Toxic Activity of Escherichia coli Hemolysin

Abstract: Hemolysin of Escherichia coli is activated by fatty acylation of the protoxin, directed by the putative acyl transferase HlyC and by acyl carrier protein (ACP). Mass spectrometry and Edman degradation of proteolytic products from mature toxin activated in vitro with tritium-labeled acylACP revealed two fatty-acylated internal lysine residues, lysine 564 and lysine 690. Resistance of the acylation to chemical treatments suggested that fatty acid was amide linked. Substitution of the two lysines confirmed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
196
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 32 publications
4
196
0
2
Order By: Relevance
“…In cases where it has been studied, sites of palmitoylation in vivo and in vitro are the same (Bizzozero et al, 1987;Gutierrez and Magee, 1991;Stanley et al, 1994). In most cell-free systems, palmitoylating activity is dramatically reduced if membranes are pretreated by boiling (Berger and Schmidt, 1984;Slomiany et al, 1984), suggesting an enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where it has been studied, sites of palmitoylation in vivo and in vitro are the same (Bizzozero et al, 1987;Gutierrez and Magee, 1991;Stanley et al, 1994). In most cell-free systems, palmitoylating activity is dramatically reduced if membranes are pretreated by boiling (Berger and Schmidt, 1984;Slomiany et al, 1984), suggesting an enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, we chose to study porcine brain tubulin that was palmitoylated in a cell-free system (Caron, 1997). In support of this decision, studies of other proteins have shown that sites of palmitoylation in vivo and in vitro are equivalent (Bizzozero et al, 1987;Gutierrez and Magee, 1991;Stanley et al, 1994). Different methodologies for protein structure analysis have been used to identify palmitoylated amino acids (Papac et al, 1992;Weimbs and Stoffel, 1992;Bizzozero et al, 1994a;Hackett et al, 1994 (Ozols, 1984), necessitating the use of gel filtration on Sephadex LH60.…”
Section: Proteinsmentioning
confidence: 99%
“…Cysteine residues are the primary sites of palmitoylation. However, serine, threonine, and lysine residues may also be palmitoylated (for review, see Bizzozero et al, 1994b;Hackett et al, 1994;Stanley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (Stanley et al, 1994) has shown that the two specific sites for HlyC-dependent acylation are located 288 and 414 residues, respectively, upstream of the C-terminal secretion signal. Involvement of the C terminus in the acylation reaction seems extremely unlikely, since HlyA lacking the N-terminal part containing the proposed amphipathic helices, or deletion of the Cterminal part, which contains the secretion signal, were still acylated normally in vitro (Stanley et al, 1994). Despite many detailed genetic and biochemical studies of the properties of HlyA and its interaction with membranes, no evidence has been presented in the literature to indicate that the C terminus of HlyA is directly involved in haemolytic activity.…”
Section: Discussionmentioning
confidence: 99%